Signing a Bilateral Investment Treaty - A tradeoff between investment protection and regulation - Chen Li (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We develop a theoretical model of bilateral investment treaties (BITs) to analyze their effects on firm profits and government welfare with heterogeneous firms. We explicitly model the trade-off between attracting foreign direct investment (FDI) and protecting the government's scope to regulate. We show that BITs can improve overall efficiency by internalizing externalities, but with firms gaining at the government's expense. The efficiency improvement does not hold for less profitable industries. We also show that attracting new FDI through a BIT may decrease welfare, while the protection of existing FDI unambiguously raises it. We propose redesigning BITs by including a tax on firm profits, in order to redistribute gains from a BIT such that both firms and the government see a Pareto improvement. In an empirical exercise, we estimate the expected annual cost for Germany resulting from an EU-US BIT to be 27mn, and the compensating profit tax to be 0.5%.
Keywords: F21; F23; F53; 330